Changing priorities in climate change research and adaptation policy - Lykke E. Andersen (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2015)
This month is likely to be one of the hottest on record, with a very strong El Ni\~no adding to more than a century of global warming. Two of the five global temperature indices already broke records in October 2015 (NASA-GISS and NCDC), and the remaining three also show a clear upward jump due to the strong El Ni\~no this Christmas (see www.climate4you.com for up-to-date climate indicators). These record events could help favor a positive outcome at the twenty-first session of the Conference of the Parties (COP21) in Paris this month. However, even if the COP21 turns out to be exceptionally successful in securing worldwide commitments to reduce CO2 emissions, this would have an almost imperceptible effect on our vulnerability to climate events over the rest of this century. According to standard model simulations (using the MAGICC model), all the mitigation policies promised by the US, China, the EU and the rest of the world, implemented from the early 2000s to 2030 and sustained through the century are likely to reduce global temperature rise by about 0.17êC in 2100 (Lomborg, 2015). Add to that the fact that climate change constitutes only a small fraction of all our climate related problems (see following sections), and an even smaller fraction of all the problems and risks that we continually face (accidents, disease, wars, terrorism, unemployment, pests, earthquakes, volcanic eruptions, price fluctuations, etc.), one must conclude that climate change mitigation policies, however successful, will only solve a small part of our problems. Much more will be needed to increase resilience. As evidenced in this policy brief, this realization is beginning to penetrate the most recent literature on adaptation policy.
Keywords: 330